Physical habitat structure in marine ecosystems: the case study of Reyna Bay, Constanța (Geo-Eco-Marina, 2024)
Reyna Bay, an artificial bay on the northern Romanian Black Sea coast near Constanța, underwent significant modifications between 2015 and 2016 to protect against erosion. Reinforced embankments and submerged spur dikes were installed to stabilize the shoreline, while newly added sand with a high shell fragment content can mitigate sediment loss. This study focuses on habitat mapping in Reyna Bay, covering an area of 400 m in width and extending up to a kilometre beyond the bay.Habitat mapping is crucial for understanding the distribution of marine habitats, especially in areas where coastal interventions alter natural processes. This research aims to provide a detailed habitat map of the bay using a combination of modern remote sensing techniques, including acoustic classification methods for seabed sediments. By integrating bathymetric, sedimentological, and biological data, the study not only assesses current seabed conditions but also contributes to European marine biodiversity efforts through data-sharing initiatives, such as the European Marine Data Portals and the EUNIS classification system.The primary objective of this study is to classify and map seabed habitats using advanced technologies such as multibeam and singlebeam echosounders, sidescan sonar, and sediment sampling. The collected data was validated through ground truthing and biological sampling, ensuring an accurate habitat classification. By studying the area both within and outside of the bay, this research reveals how recent coastal modifications have influenced sediment distribution and habitat structure.
Keywords: physical habitat mapping; geophysical measurements; Romanian Black Sea Coast